2014
DOI: 10.1186/1751-0147-56-23
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics in female Swedish moose (Alces alces), with emphasis on puberty, timing of oestrus, and mating

Abstract: BackgroundThe moose (Alces alces) is an intensively managed keystone species in Fennoscandia. Several aspects of reproduction in moose have not been fully elucidated, including puberty, timing of mating and oestrus, and the length of the oestrus period. These aspects are relevant for an adaptive management of moose with respect to harvest, population size, demography and environmental conditions. Therefore, an investigation of female moose reproduction was conducted during the moose-hunting period in southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the present study, the mean testes weight decreased over the time period studied, indicating that a decline in sperm production and quality also takes place in moose bulls, which in turn indicates that the peak rut is over by the time the hunting period commences. This is supported by the findings of the timing of oestrus in female moose, where most adult females show oestrus just prior to the start of the hunting period in moose in southern Sweden (Malmsten et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the present study, the mean testes weight decreased over the time period studied, indicating that a decline in sperm production and quality also takes place in moose bulls, which in turn indicates that the peak rut is over by the time the hunting period commences. This is supported by the findings of the timing of oestrus in female moose, where most adult females show oestrus just prior to the start of the hunting period in moose in southern Sweden (Malmsten et al, 2014).…”
Section: Discussionmentioning
confidence: 64%
“…Reproductive season in terms of the oestrus period, from the end of September to the beginning of October has been reported in moose (Garel et al, 2009;Haagenrud and Markgren, 1974;Markgren, 1969;Monfort et al, 1993;Schwartz and Hundertmark, 1993). However, a recent Swedish study (Malmsten et al, 2014) showed that some young adults, (or old cows with low body weight) did not have their first oestrus of the season until the end of October/beginning of November. The results of the present study indicate that mating during the latter part of October or beginning of November (during a late first oestrus or a second oestrus) may result in lower conception rates due to lower sperm quality since we found that the PNS decreased over time.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Sweden, the moose rut overlapped with the hunting period (Malmsten et al ). We tested whether observed patterns in moose movement behavior are due to behavioral changes in moose during the rut or due to hunting disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…For many deer species, the rut is in fall. During the rut, female deer are in estrus and male deer modify their behavior to maximize their chances for mating (Mysterud et al , Malmsten et al ). In some deer species (e.g., moose, Bubenik , Leblond et al ; Columbian black‐tailed deer [ Odocoileus hemionus columbianus ], Long et al ; white‐tailed deer, Foley et al ), males intensify their movement possibly searching areas more effectively to find suitable mating partners.…”
mentioning
confidence: 99%